Akulturasi Politik Dalam Dunia Dakwah - Andri Nirwana. AN (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Despite many differences, da'wah and politics are intersecting. Da'wah activities often touch politics, while political activities often become a media propaganda. However, some people disagree to consolidate da'wah with politics considering that both have different intentions. Politics aims for the power. The da'wah, on the other hand, is a call to all people to follow the path of God through the promotion of good deeds and prohibition of bad deeds. It has a realistic objective, conveying religious messages to the mankind. In contrast to the statements, this article asserted that da'wah and politics can be combined by treating the politics as a means to convey the da'wah. Da'wah, in its administration, can use a variety of media, including the power. Yet, the power should not be the purpose of da'wah. Da'wah is closely associated with politics. When rules of a country are hostile to Islam, the policy can suppress the Muslims. The relation between politics or power and da'wah will help accelerate the objective attainment of the da'wah. It is true that da'wah can progress without the support from powerful organizations or the state, but its success is different when compared to the results of the da'wah supported by a strong organization or the state.